Analysis of tapetally expressed genes during Arabidopsis thaliana pollen development - Nkrumah-Buansi, Martha (2013)
The formation of viable pollen relies upon a complex interaction of genes in time and space within the anther. One of the most important maternal tissues involved in the production of functional pollen is the tapetum, which is a highly active tissue that plays a major secretory role during pollen development. This project involved the molecular analysis of genes that are expressed in the anther tapetum and are critical for functional pollen development. A number of these are thought to be regulated by, or interact with MALESTERILITY1 (MS1), a transcriptional regulator of male gametogenesis (Yang et al., 2007) or ABORTED MICROSPORE (Xu et al., 2010). Work involved analysis of an ABC transporter (At3g13220), which has been shown to be critical for viable pollen formation and confirmed as directly regulated by AMS (Xu et al., 2010). Another protein, POB2, which appears to be involved in ubiquitin-based proteolytic breakdown, is thought to interact with the MS1 protein. POB2 was identified from a previous screen of a stamen specific yeast-2-hybrid library using the MS1 protein. This interaction has been subsequently confirmed in this work by further yeast two hybrid analyses and bifunctional fluorescent complementation. Further work involved verification of this interaction in vitro and in planta by pull-downs and transient expression of proteins in E. coli and Nicotiana benthamiana respectively. Other work focused on identifying factors that regulate MS1 expression; this identified novel male sterile mutants derived from screening fast neutron mutagenised seed carrying the MS1Prom:MS1-GFP functional fusion protein. Microscopic observation of the fluorescent reporter showed changes in the stage specific expression of MS1 in some of these mutants. Backcrossing of the male sterile mutants with the parental plants (carrying the MS1Prom:MS1-GFP fusion construct) and the ms1 mutant confirmed one as a new mutant and the other three as being allelic to the ms1 mutation. Gene mapping of this mutant was subsequently conducted and suggest that it may be located on chromosome 3. These results are providing insight into the regulatory network of MS1 and AMS during anther development.